Assessment of Inter-character Correlations in Pterocarpus marsupium, An Endangered Medicinal Plant of Tropical forest - Mohammad, Naseer; Mishra, Yogeshwar; Ansari, S. A. (Indian Forester, 2013)
In the present study, attempts were made to find out the parameters for selection of superior trees of Pterocarpus marsupium. The studies associated with correlation and path analysis, indicated clearly that clear bole height, girth at breast height and total plant height were the most important parameters which could be considered for selection of superior plants of this species. In fact, it would be appropriate if these parameters are incorporated in developing strategy for selection and genetic improvement of the species.